Folic Acid–Modified miR-491-5p–Loaded ZIF-8 Nanoparticles Inhibit Castration-Resistant Prostate Cancer by Regulating the Expression of EPHX1 - Ju, Guanqun; Liu, Bing; Ji, Mingfei; Jin, Rui; Xu, Xiaojian; Xiao, Yongshuang; Li, Jie; Xu, Dongliang; Huang, Yuhua; Hou, Jianquan (Frontiers in Bioengineering and Biotechnology, 2021)
EPHX1 has been reported to play an important role in the development of a variety of tumors. However, the research of EPHX1 regulating the development of castration resistant prostate cancer (CRPC) has not been reported. We used proteomics technology found that the protein of EPHX1 is highly expressed in prostate cancer tissues and human castration resistant prostate cancer cell line (C4-2 cell). We screened and proved that EPHX1 is the direct target of miR-491-5p. High expression of miR-491-5psignificantly reduce the level of EPHX1 in C4-2 cellsand inhibit the clone formation, proliferation and migration of C4-2 cells. We synthesized ZIF-8 nano drug vectors to deliver miR-491-5p into C4-2 cells. After loading miR-491-5p into ZIF-8, we modified the surface of ZIF-8 with FA as the target group (FA@ZIF-8). Our synthesized nanomedicine carrier showed little cytotoxicity to C4-2 cells even at 200 ug/mL concentration. The modified FA could increase the efficiency of nanomaterials entering into C4-2 cells. FA@miR-491-5p@ZIF-8 can stably release miR-491-5p for a long period both in phosphate-buffer saline (pH 7.4) and acetate buffer (pH 4.8) and miR-491-5p released faster in the beginning of the experiment in acetate buffer (pH 4.8). FA@miR-491-5p@ZIF-8 significantly reduces the colony formation, cell proliferation and migration of C4-2 cells and FA@miR-491-5p@ZIF-8 has better effect than miR-491-5p alone.In vivo, the results showed that FA@miR-491-5p@ZIF-8 significantly inhibit the growth of prostate cancer. In short，this studyverified that miR-491-4p regulate the development of CRPCby target EPHX1. The drug nanocarrier FA@miR-491-5p@ZIF-8not only significantly reduced the clone formation, cell proliferation and cell migration of C4-2 cells, but also significantly inhibited the growth of solid tumor. Our research provides a theoretical basis and treatment strategy for CRPC.